Pemanfaatan Listrik Tenaga Surya Sebagai Pasokan Listrik Untuk Menghidupkan Lampu Pju Lapangan Sarana Olah Raga Masyarakat Warga RT 002/05 BTN Cantiga Petir Cipondoh Tangerang - Heri Suyanto (Terang, 2021)
This article was prepared based on the Community Service Institute (PKM) of the 2019 PLN Institute of Technology which was carried out in the field of sports facilities for residents of RT002 / 05 BTN Cantiga Petir Cipondoh Tangerang with problems of frequent illegal connection or theft of electricity from electric poles for street lighting and there are still locations that require street lighting. The Purpose of Community Service Activities (PKM) This is so that the public can know the use of Solar Electricity for the community and as an implementation with theory and practice is applied to the public about the development of solar electricity technology in current energy. Through this activity, the community of Cipondoh Lightning Cantiga residents learned about the use of solar electricity for the surrounding community to turn on the PJU Lights in the RT 002/05 BTN Cantiga Petir Cipondoh Tangerang Sports Field.